Shakespeare bats cleanup - Koertge, Ronald (Candlewick Press, 2006)
When a fourteen-year-old baseball player catches mononucleosis, he discovers that keeping a journal and experimenting with poetry not only helps fill the time, it also helps him deal with life, love, and loss.